Modern characteristic of water balance of river basins in the West Siberia Southeast - Artem O. Eliseew; Sergey G. Kopysov (Водное хозяйство России: проблемы, технологии, управление)
The structure of the water balance provides an evident representation on the possibilities of practical use of water resources. The relevance of the study is caused by the lack of current data on the water balance of river basins. For example, for the Middle Ob basin, there are data only in the monograph “Surface Water Resources of the USSR” published in 1972, in which evaporation was defined as the difference between the interpolated precipitation and runoff depth measured in the control station. Modern water balance studies require physically based modeling on large-scale raster cells characterized by climatic and landscape parameters. The purpose of the article is to provide stakeholders with current data on the average longterm structure of the water balance for 56 river basins in the West Siberia Southeast located in the Tomsk, Kemerovo and Novosibirsk regions.